Subsurface and solid solution-type defect engineering in the CoCr2O4–Bi2WO4–NiS2 nanocomposite for the visible-light degradation of doxycycline and removal of chromium and its genotoxic evaluation in Allium cepa. (16th August 2022) - Balasurya, S.; Okla, Mohammad K.; Al-amri, Saud S.; Alaraidh, Ibrahim A.; Al-ghamdi, Abdullah A.; Soufan, Walid; Abdel-Maksoud, Mostafa A.; Abdelaziz, Ramadan F; Studenik, Christian R.; Khan, S. Sudheer
Abstract : The double Z-scheme subsurface and solid solution-type defect engineering in CoCr2 O4 –Bi2 WO4 –NiS2 nanocomposite allow it to be used for the treatment of contaminated environmental water. Abstract : In the present work, ternary CoCr2 O4 –Bi2 WO4 –NiS2 nanocomposite (CCO–BWO–NS NC), a semiconductor photocatalyst, was prepared for the effective mineralization of doxycycline and photocatalytic removal of Cr(vi ). Here, the modification of BiO–WO4 –BiO (BWO) as a sandwich structure caused higher lattice oxygen vacancies. The decoration of NiS2 (NS) on CCO–BWO enhanced the photocatalytic activity of the NC under visible-light irradiation. The photocatalytic degradation efficiency of doxycycline (doxy) and removal of Cr(vi ) by the CCO–BWO–NS NC was found to be 99.8% and 94.7%, respectively. The subsurface and solid solution-type defect engineering was determined by X-ray photoelectron spectroscopy (XPS). Density function theory (DFT) calculations enabled the band structure and defect mechanism of the CCO–BWO–NS NC to be determined. Further, the photocatalytic efficiency was studied by varying the pH in the degradation of doxy and removal of Cr(vi ). The total organic carbon (TOC) reduction after doxy photodegradation was found to be 98.6%. In addition, the genotoxicity of the CCO–BWO–NS NC was determined and the results showed that the CCO–BWO–NS NC had a comparatively lower genotoxicity and mitotic index, and no micronuclei were observed. Thus, the prepared CCO–BWO–NS NC was found be an excellent photocatalyst for the effective removal of doxy and Cr(vi ). The study suggests that the CCO–BWO–NS NC could be an excellent photocatalyst for environmental water treatment.